PHYSICAL CHARACTERISTICS, SENSORY EVALUATION, AND AMINO ACID CONTENT OF POWDERED OVER FERMENTED MLANDING TEMPEH - Asri Nursiwi; Dwi Ishartani; Ardhea Mustika Sari; Nur Ayu Istiqomah (Jurnal Teknologi dan Industri Pangan, 2021)
Mlanding tempeh is non-soybean tempeh made from ripe lamtoro (Leucaena leucocephala) seed. In Wonogiri, an area in Indonesia, over fermented mlanding tempeh (OFMT) is often used as a seasoning for traditional food since it produces a special taste. OFMT is also dried to extend the shelf life, making it easier to use as a seasoning. This research aims to study the physical characteristics, sensory evaluation, and amino acid content of powdered over fermented mlanding tempeh (POFMT). The drying of the OFMT used a cabinet dryer with variations in drying temperatures of 55, 60, and 65°C for eight hours. Then, it was mashed and sifted to obtain POFMT. The obtained powder was then analyzed for its physical characteristics in yield, water absorption capacity, solubility, bulk density, sensory evaluation with the hedonic test, and amino acid content. This study found that different drying temperatures significantly affected the yield and water absorption but did not significantly affect the solubility and bulk density. The yield values varied between 7.06-12.92%; water absorption capacity varied between 0.36-0.55 g/g; solubility varied between 36.45-41.33%; bulk density varied between 0.38-0.42 g/mL. The sensory evaluation results showed that the panelists' preference for POFMT with variations in drying temperature was not significantly different. In addition, the amino acid content of POFMT varied between 0.99-5.43% (db), with the highest levels being glutamic acid and aspartic acid.